Value Based Quality Engineering Education - Gupta, Ajit Kumar (Journal of Engineering Education Transformations, 1999)
The economic progress of a country IS strongly linked with the quality of education, specially with the technical education. Also the quality of life of society at large and the individuals in the society, largely depends upon the quality of education.